Prevention of Nephrotoxicity Induced by Cyclosporine‐A: Role of Antioxidants. Issue 3 (March 2015) - Damiano, Sara; Ciarcia, Roberto; Montagnaro, Serena; Pagnini, Ugo; Garofano, Tiziana; Capasso, Giovambattista; Florio, Salvatore; Giordano, Antonio
ABSTRACT Cyclosporine A (CsA) is a powerful immunosuppressive drug used to prevent allograft rejection after organ transplantation as well as in human and veterinary medicine. Unfortunately, its use is hampered by its nephrotoxic effects. The mechanisms of CsA‐induced hypertension and nephrotoxicity are not clear, but several studies suggest the possible involvement of free radicals. In this review we have summarized the effect of some antioxidants that we have used in the recent years, in combination with CsA, to better understand the exact mechanism of action of CsA and to try to open new perspectives in the treatment of CsA nephrotoxicity. J. Cell. Biochem. 116: 364–369, 2015. © 2014 Wiley Periodicals, Inc.